The Role of Explicit Interactive Metadiscourse Markers’ Instruction in Iranian EAP Learners’ Reading Comprehension - Fatalaki, Javad Ahmadi; Amini, Ehsan; Mirzaee, Meysam (Lesya Ukrainka Eastern European National University, 2014)
This research was conducted to investigate the role that explicit instruction of interactive metadiscourse markers plays in Iranian EAP learners’ reading comprehension performance. To this end, 36 students of business management in intermediate level of English language proficiency, both male and female, were asked to participate in this study. They, subsequently, were divided into two groups of equal size, that is, control and experimental. Prior to presenting the treatment to the experimental group, all the participants were given a reading comprehension test. Then, the learners in the experimental group were explicitly taught interactive metadiscourse markers in 10 allocated sessions. Meanwhile, students in the control group of the study were taught through the typical method of the university. Afterward, the students of both groups were given the previously used reading comprehension test again. Statistical analyses of the t-test revealed that those in the experimental group outperformed significantly in the post-test phase of the study (p<0.01). Therefore, it can be inferred that explicit instruction of interactive metadiscourse markers has the outstanding beneficial role in EAP learners’ reading comprehension.
Keywords: interactive metadiscourse markers; reading comprehension; EAP learners; explicit instruction